Can Robots Keep You Upright? An Ergonomic Analysis of Surgeon Posture in Robotic Versus Conventional Total Knee Arthroplasty - Zachary Gapinski; Eric Mason; Ezan Kothari; Pratik Desai; George Haidukewych; Cody Green (Surgeries)
Background: Robotic-assisted technology has become an increasingly utilized adjunct within the realm of primary total knee arthroplasty (TKA). Previous studies have shown that robotic-assisted total knee arthroplasty (raTKA) offers potential advantages of enhanced bony preparation and optimal implant alignment with equivalent long-term patient outcomes and component longevity in comparison to conventional TKA (cTKA). Furthermore, recent studies have identified the additional benefit of decreased surgeon physiologic stress with the use of raTKA. The purpose of this study was to compare differences in surgeon posture between primary raTKA and cTKA. Materials and Methods: We prospectively evaluated 103 consecutive primary TKA cases (48 raTKAs, 55 cTKAs) performed by three high-volume, fellowship-trained arthroplasty surgeons. Throughout each case, surgeons wore a posture-tracking device to evaluate time spent slouching. The threshold for slouching was set to 30 degrees of flexion from a neutral spinal axis. Demographic and operative factors were collected. Two-tailed tests and multivariate analysis were used to assess for differences between groups. Results: After controlling for individual surgeon differences in posture, we found a decrease in the percentage and duration of time spent slouching in raTKA cases compared to cTKA cases (42.4 vs. 72.5%, p < 0.001, 35.4 vs. 54.7 min, p = 0.037). On average, the use of the robot decreased surgeon slouching time by 19.3 min (26.6%, p < 0.001). Patient factors such as increased age and ASA 2 were also associated with favorable effects on posture (p < 0.001). Conclusions: Surgeons performing primary raTKA cases spend significantly less case time and case percentage in a slouched posture compared to conventional primary TKA cases. This suggests the potential for ergonomic benefit of robotic-assisted technology in primary TKA. Further research is needed to determine the long-term effects of posture on surgeon pain and career longevity.